Keteladanan Orangtua dalam Perspektif Pendidikan Islam untuk Anak - Sulaiman W.; Sulaiman Ismail (Journal of Education and Teaching (JET), 2024)
This article aims to elucidate the principles of parental exemplarity as an educational model from the perspective of Islamic education. The presence of parents as primary educators and central figures within the household holds significant importance. However, a fundamental challenge that arises is the lack of understanding among some parents regarding their role and responsibility as role models, which can inadvertently lead children to emulate undesirable behaviors. This research employs the "Library Research" method with a qualitative interpretative approach to analyze various documents, including books and journals. From the analysis, it is concluded that the concept of parental exemplarity in Islamic education can be implemented through several steps, including: 1) Instilling exemplar habits in behavior; 2) Consistently providing advice to children; and 3) Cultivating exemplarity habits from an early age, such as expectant mothers habituating positive practices. This article provides a profound understanding of how parents can effectively serve as models in educating their children in accordance with the principles of Islamic education